2012
DOI: 10.1371/journal.pone.0051397
|View full text |Cite
|
Sign up to set email alerts
|

Binding of TCR Multimers and a TCR-Like Antibody with Distinct Fine-Specificities Is Dependent on the Surface Density of HLA Complexes

Abstract: Class I Major Histocompatibility Complex (MHC) molecules evolved to sample degraded protein fragments from the interior of the cell, and to display them at the surface for immune surveillance by CD8+ T cells. The ability of these lymphocytes to identify immunogenic peptide-MHC (pMHC) products on, for example, infected hepatocytes, and to subsequently eliminate those cells, is crucial for the control of hepatitis B virus (HBV). Various protein scaffolds have been designed to recapitulate the specific recognitio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2018
2018
2018
2018

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 58 publications
(70 reference statements)
0
3
0
Order By: Relevance
“…Affinity of FKS-D11P TCR (K D value of 4.70 × 10 −9 mol/L) was much higher than that of naturally occurring TCR binding to HLA class I/peptides (K D value of 1-50 × 10 −6 mol/L). 21 In previous studies on a soluble TCR-multimer, K D values of TCR for HLA-A2/HTLV type 1 Tax [11][12][13][14][15][16][17][18][19] , HLA-A2/HBV env [183][184][185][186][187][188][189][190][191] , HLA-A2/MART1 26-35(A27L) and HL A-A2/NY-ESO-1 157-167(C165V) were 1.06 × 10 −6 , 0.6 × 10 −6 , 5.4 × 10 −6 and 4.3 × 10 −6 mol/L, respectively. 17,19,20 These results suggested that the affinities of successfully constructed soluble TCR were also higher than the general affinity of TCR.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Affinity of FKS-D11P TCR (K D value of 4.70 × 10 −9 mol/L) was much higher than that of naturally occurring TCR binding to HLA class I/peptides (K D value of 1-50 × 10 −6 mol/L). 21 In previous studies on a soluble TCR-multimer, K D values of TCR for HLA-A2/HTLV type 1 Tax [11][12][13][14][15][16][17][18][19] , HLA-A2/HBV env [183][184][185][186][187][188][189][190][191] , HLA-A2/MART1 26-35(A27L) and HL A-A2/NY-ESO-1 157-167(C165V) were 1.06 × 10 −6 , 0.6 × 10 −6 , 5.4 × 10 −6 and 4.3 × 10 −6 mol/L, respectively. 17,19,20 These results suggested that the affinities of successfully constructed soluble TCR were also higher than the general affinity of TCR.…”
Section: Discussionmentioning
confidence: 97%
“…So far, results of several studies aimed at the development of a TCR multimer have been reported. However, most of the TCR were directed to viral antigens, human T‐cell leukemia virus type 1 tax, HIV‐gag and HBV env . Regarding a TAA‐specific TCR, only Bethune et al reported soluble TCR tetramers and dextramers directed to MART1 26‐35(A27L) and NY‐ESO‐1 157‐167(C165V) in the context of HLA‐A2.…”
Section: Discussionmentioning
confidence: 99%
“…Since Andersen et al, first produced a mAb with TCR specificity (43), there have been over 60 TCRlike mAbs generated against HLA class I complexes. For most of these TCR-like mAbs, it is not clear which specific portions of their target peptide are crucial for recognition (33,34,36,37,(44)(45)(46)(47)(48)(49)(50)(51)(52)(53)(54)(55)(56)(57). Thus, even though these mAbs recognize a given pHLA, it may not be entirely specific, and any cross-reactivity against similar pHLA can lead to severe or lethal consequences when used in patients (31,58).…”
Section: Discussionmentioning
confidence: 99%